THE PLACE OF ANIMALS IN THE SYSTEM OF PROPERTY RIGHTS - Zhusipova Бакыт Акылбаевна; Mukasheva Анар Абайханкызы; Abdrassulov Ермек Баяхметович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The article provides a general analysis of regulatory legal acts and scientific literature that consolidate the specifics of the legal regime of animals, including on the basis of an analysis conducted taking into account international experience. Topical issues of responsibility in the handling, use and maintenance of animals are considered. Special attention is also paid to the analysis of the place of animals in the system of objects of civil law. The issue of animal ownership is insufficiently developed and complex, and therefore legal conflicts often arise in society. The form of ownership from the "animal world" to the category of other animals has been clarified. In society, most owners forget that when dealing with animals, there is a moral principle enshrined in civil legislation, animals must be treated with great responsibility. Currently, numerous violations are allowed that cause great harm to animals. The authors raise the issue of the lack of a unified approach to the classification of animals in the current legislation and scientific literature. In the matter of defining the concept of animals, it is necessary to have a general understanding that the object of animal ownership is not an inanimate object. To regulate the legal status of animals in the Civil Code, their processing is being updated and modernized, changes are required to ensure its compliance with the needs of society. As well as amendments and additions to the national legislation, including taking into account the specific features associated with additional requirements for handling, use and keeping of animals, it is proposed to introduce a special chapter on objects of property rights into the Civil Code of the Republic of Kazakhstan.